Ancient DNA from misión Salesiana, Tierra del Fuego - Stone, Anne (2018)
Beginning in 1492 and lasting even today, the encounters between Europeans and Native American populations have had major demographic, social, biological and ecological impacts. While first discovered by Europeans in 1520, European settlement of Tierra del Fuego did not begin until the second half of the 19th century. Analysis of biological data from a cemetery population at Misión Salesiana (?Nuestra Señora de la Candelaria?) in Tierra del Fuego provides insight into the local population history in this region of South America after contact. Misión Salesiana was established in 1893 to assimilate and Christianize the remaining local indigenous population, the Selk?nam. The mission cemetery includes burials from the community as well as the mission, averaging ~100 years old. Samples of tooth and bone from 32 individuals were used for DNA extraction. In-solution hybridization capture was successfully used to recover the mitochondrial genomes from 25 individuals. Mitochondrial lineages C and D are predominately represented in the sample (appearing in 50% and 41% of the individuals, respectively). Two individuals have haplotypes which are found in European populations, which is reflective of either admixture or interment of European individuals in the mission cemetery. The whole mitochondrial genome data were analyzed for measures of diversity and the cemetery population was compared to other South American populations, both ancient and modern. These studies of diversity yield insight into both inter and intra group variation in Native South American populations. Genome-wide SNP analyses are currently in progress.